Integrating Material Circularity and Green Logistics Indicators in Supply Chain Performance Measurement Using the Green SCOR Model - Alina Cynthia Dewi; Maria Fiore Winni Kristianes; Mohammad Rachman Waluyo; Nurfajriah (Politeknik APP Jakarta, 2026)
Integrating environmental considerations into supply chain performance measurement has become increasingly critical, growing sustainability and corporate responsibility. In the textile industry, particularly the non-woven sector, complex activities and mounting environmental pressures underscore the need for sustainability-oriented evaluation. The company lacks a supply chain performance measurement system that considers environmental aspects, creating a research gap that this study addresses. This study evaluates supply chain performance by embedding environmental dimensions into the measurement framework. The research was conducted in four stages: (1) identifying indicators through the Content Validity Index; (2) weighting indicators using the Analytic Hierarchy Process; (3) assessing performance with the Objective Matrix; and (4) classifying priorities through the Traffic Light System. A total of 22 validated indicators were applied, including three green indicators: Recycled Material Usage, Reusable Material, and Truck Load Optimization Rate. Recycled Material Usage was introduced as a novel indicator and validated as contextually significant for industrial supply chains. Results show a 2024 performance score of 5.678, classified as yellow under the Traffic Light System with five indicators as critical priorities for improvement. This study provides a regular monitoring tool that enables managers to establish a sustainable supply chain.